The Decrease in Mitochondrial DNA Mutation Load Parallels Visual Recovery in a Leber Hereditary Optic Neuropathy Patient - Emperador, Sonia; Vidal, Mariona; Hernández-Ainsa, Carmen; Ruiz-Ruiz, Cristina; Woods, Daniel; Morales-Becerra, Ana; Arruga, Jorge; Artuch, Rafael; López-Gallardo, Ester; Bayona-Bafaluy, M. Pilar; Montoya, Julio; Ruiz-Pesini, Eduardo (Frontiers in Neuroscience, 2018)
The onset of Leber hereditary optic neuropathy is relatively rare in childhood and, interestingly, the rate of spontaneous visual recovery is very high in this group of patients. Here, we report a child harboring a rare pathological mitochondrial DNA mutation, present in heteroplasmy, associated with the disease. A patient follow-up showed a rapid recovery of the vision accompanied by a decrease of the percentage of mutated mtDNA. A retrospective study on the age of recovery of all childhood-onset Leber hereditary optic neuropathy patients reported in the literature suggested that this process was probably related with pubertal changes.